A computational aeroelastic framework based on high-order structural models and high-fidelity aerodynamics - Grifò, Marco; Da Ronch, Andrea; Benedetti, Ivano (Aerospace science and technology, 2023)
A computational framework for high-fidelity static aeroelastic analysis is presented. Aeroelastic analysis traditionally employs a beam stick representation for the structure and potential, inviscid and irrotational flow assumptions for the aerodynamics. The unique contribution of this work is the introduction of a high-order structural formulation coupled with a high-fidelity method for the aerodynamics. In more details, the Carrera Unified Formulation coupled with the Finite Element Method is implemented to model geometrically complex composite, laminated structures as equivalent bi-dimensional plates. The open-source software SU2 is then used for the solution of the aerodynamic fields. The in-house fluid-structure coupling algorithm is based on the Moving Least Square technique. The paper contains a thorough validation of each disciplinary solver of the aeroelastic framework, and provides a few application test cases. For an unswept, untapered and isotropic wing, it was found that the method provides results in agreement with predictions from models based on potential flow theory for moderate freestream velocities. Departures were reported for very low speed and in the high-subsonic regime, alerting the need of adopting high-fidelity flow solutions at these flow conditions. The computational framework was then applied to the static aeroelastic tailoring of a composite wing. The paper concludes providing an overview of future implementation steps towards a tool for the seamless analysis of composite structures subject to different flow conditions, from low to high speed.